2009
DOI: 10.1073/pnas.0907518106
|View full text |Cite
|
Sign up to set email alerts
|

Fibronectin forms the most extensible biological fibers displaying switchable force-exposed cryptic binding sites

Abstract: Rather than maximizing toughness, as needed for silk and muscle titin fibers to withstand external impact, the much softer extracellular matrix fibers made from fibronectin (Fn) can be stretched by cell generated forces and display extraordinary extensibility. We show that Fn fibers can be extended more than 8-fold (>700% strain) before 50% of the fibers break. The Young's modulus of single fibers, given by the highly nonlinear slope of the stressstrain curve, changes orders of magnitude, up to MPa. Although m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

16
301
2
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 245 publications
(320 citation statements)
references
References 37 publications
(68 reference statements)
16
301
2
1
Order By: Relevance
“…A recent report suggested that FN nanofibers formed from a droplet exhibited a complete elastic recoil, even after large extensions (λ = 3.5); 22 however, we argue that this observation is dependent on the fabrication method. Due to the nature of their synthesis, these fibers pulled from a droplet 22 experience a pre-stretch of λ = 2.4, as they are deposited prior to mechanical testing.…”
contrasting
confidence: 67%
See 2 more Smart Citations
“…A recent report suggested that FN nanofibers formed from a droplet exhibited a complete elastic recoil, even after large extensions (λ = 3.5); 22 however, we argue that this observation is dependent on the fabrication method. Due to the nature of their synthesis, these fibers pulled from a droplet 22 experience a pre-stretch of λ = 2.4, as they are deposited prior to mechanical testing.…”
contrasting
confidence: 67%
“…1,[17][18][22][23] We measured the temporal changes in fluorescence resonance energy transfer (FRET) intensity before, during, and after the labeled fabrics were released from the PIPAAm substrate (Figure 2a). We observed an exponential increase in the ratio between the acceptor and donor emission intensities (I A /I D ) until fabrics were freed from the PIPAAm substrate and contraction was completed (t= 560 sec, Figure 2b We asked how the secondary structural changes of FN affect the bulk mechanical properties of the released FN fabrics.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, forces emanating from contractile cells such as pathogenic myofibroblasts have been hypothesized to partially unfold ECM proteins like Fn, thus engaging/disengaging theorized integrin switches (25). Despite considerable in silico and in vitro evidence for the extensibility of Fn within fibers and Fn type III domain unfolding (26)(27)(28), there is still no direct evidence that such molecular events occur in vivo, a fact that perpetuates the debate regarding the validity of such observations.…”
Section: Discussionmentioning
confidence: 92%
“…20,21 Other ways to induce the formation of fibronectin fibrils on material surface, mostly triggered by force, have been reported elsewhere. 20,[23][24][25] Here, a series of copolymers with controlled ethyl acrylate/methyl acrylate (EA/MA) ratio were synthetised seeking to modulate the degree of FN fibrillogenesis. We investigated FN adsorption and conformation as a function of the amount of EA in the copolymers.…”
Section: Introductionmentioning
confidence: 99%